1977
DOI: 10.1128/aem.34.2.185-188.1977
|View full text |Cite
|
Sign up to set email alerts
|

Production of beta-galactosidase from Streptococcus thermophilus grown in whey

Abstract: Galactosidase (EC 3.2.1.23) was extracted from Streptococcus thermophilus grown in deproteinized cheese whey. Cultural conditions optimum for maximum enzyme production were pH 7.0, 40°C, and 24 h. Proteose peptone (2.0%, wt/vol) and corn steep liquor (2.8%, wt/vol) were highly stimulatory, increasing the enzyme units available in their absence from 660 U/liter of medium to 18,200 and 10,000 U/liter of medium, respectively, in their presence. There was an insignificant increase in the production of enzyme in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
13
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 9 publications
10
13
0
Order By: Relevance
“…Peptone was the best nitrogen source for the production of β-galactosidase by strain B1.1. Our results agreed with those observed for Streptococcus thermophilus and Kluyveromyces lactis by Rao and Dutta [16] and Barreto et al [5], respectively, who demonstrated that peptone can be a good nitrogen source which that a maximum synthesis of β-galactosidase. On the other hand, these results were different from the report of Domingues et al [17] and Hsu et al [9], which indicated that the highest activity of this enzyme was obtained by Aspergillus niger and Bifidobacterium longum CCRC 15708, respectively, when using yeast extract.…”
Section: Effect Of Nitrogen Source On the Production Of β-Galactosidasesupporting
confidence: 93%
“…Peptone was the best nitrogen source for the production of β-galactosidase by strain B1.1. Our results agreed with those observed for Streptococcus thermophilus and Kluyveromyces lactis by Rao and Dutta [16] and Barreto et al [5], respectively, who demonstrated that peptone can be a good nitrogen source which that a maximum synthesis of β-galactosidase. On the other hand, these results were different from the report of Domingues et al [17] and Hsu et al [9], which indicated that the highest activity of this enzyme was obtained by Aspergillus niger and Bifidobacterium longum CCRC 15708, respectively, when using yeast extract.…”
Section: Effect Of Nitrogen Source On the Production Of β-Galactosidasesupporting
confidence: 93%
“…28:119-120, 1977). The stimulating effect of growth factors in the production of lactase in other microorganisms has been reported (27,32). However, Mahoney et al (18) detected no significant changes in lactase production by Kluyveromyces fragilis grown in whey, with or without supplementation with yeast extract or corn steep liquor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this treatment could make milk, a most valuable food, available to a large number of adults and children intolerant to lactose (1,7,9,15,24,25). Preparations of lactase have been obtained from several microorganisms (3,13,20,27,30); among these, the lactose-fermenting yeasts are considered good sources of the enzyme (2,6,18,19,31,32). One of these yeasts, Candida pseudotropicalis, has been pointed out as having a good lactase potential (11,33).…”
mentioning
confidence: 99%
“…A four fold increase in enzyme production by the use of organic nitrogen sources in the medium has been reported earlier (Sonawat et al, 1981). Ramana Rao & Dutta (1977) have reported an increase in enzyme activity to the extent of nearly 28% using corn steep liquor (csl) and peptone in the enzyme production medium and concluded that addition of inorganic nitrogen or phosphorous had no significant effect in enhancing enzyme production. Corn steep liquor also contains appreciable amount of proteins and minerals as is the case with cauliflower waste (Table 2).…”
Section: Effect Of Cauliflower Waste Supplementation On B-galactosidamentioning
confidence: 61%